Congenital hypothyroidism in Turkey: a retrospective evaluation of 1000 cases - Tarım, Ömer F.; Yordam, Nurşen (The Turkish Journal of Pediatrics, 1992)
In this retrospective investigation, 1000 cases of congenital hypothyroidism followed-up in the Pediatric Endocrinology Unit at Hacettepe University Children's Hospital between 1964-1989 were evaluated with respect to age at diagnosis, main complaints, symptoms and physical findings. The mean age at diagnosis was 49.22 months, with 55.4 percent of patients diagnosed after two years of age and only 3.1 percent during the neonatal period. The main complaints of the patients were growth failure (26.7%), inability to speak (21.4%), and inability to walk (18.1%). The physical signs and symptoms most commonly detected by the physician were hypotonia (72%), constipation (66.8%), cretinoid face (64.6%), and macroglossia (64.6%). These results emphasize the necessity for routine neonatal screening programs to be established in Turkey, with the aim of detecting congenital hypothyroidism.
Keywords: congenital hypothyroidism; neonatal screening